Ecotoxicological effects of polyethylene microplastics, with and without adsorbed contaminants, on the clam Scrobicularia plana (da Costa, 1778) using a multi-biomarker approach - O’Donovan, Sarit (2019)
The potentially detrimental impacts of plastic debris on the marine biota are numerous and diverse with deleterious physical effects recorded. Microplastics, defined as plastic particles ≤ 5mm, are of particular concern due to their ubiquitous distribution in the marine environment. Low density polyethylene accounts for ~17% of European plastic production, with use dominated by the packaging industry. This study investigated the ecotoxicological effects of exposure of low density polyethylene microplastics, with and without added contaminants, in gill tissues and haemocytes of the peppery furrow shell clam, Scrobicularia plana. Environmentally relevant concentrations of contaminants, benzo[a]pyrene, oxybenzone, and perfluorooctane sulfonic acid, were adsorbed to microplastics to evaluate the potential role of plastic particles as a source of chemical contamination once ingested. S. plana were exposed to microplastics at a concentration of 1 mgL-1 for 14 days. To clarify any effects of exposure, a set of biomarkers were employed, including the quantification of antioxidant (superoxide dismutase, catalase, glutathione peroxidase) and biotransformation (glutathione-S-transferases) enzyme activities, oxidative damage (lipid peroxidation levels), genotoxicity (single and double strand DNA breaks) and neurotoxicity (acetylcholinesterase activity). Neither a genotoxic nor an inhibitory neurotoxic effect was recorded. The dominant response in catalase and glutathione-S-transferase was attributed to virgin microplastics, suggesting the observed effects were due to physical ingestion and the potential mechanical injuries that result. Superoxide dismutase and lipid peroxidation, showed an increase in activity in contaminated microplastic treatments relative to virgin microplastic, suggesting a synergistic effect of physical ingestion and chemical exposure. A reduction in glutathione peroxidase activity was observed in contaminated microplastic treatments, compared to virgin microplastic, indicating an antagonistic effect may have occurred. Further analysis is needed to confirm the bioavailability of microplastics and that the observed biomarker responses are a result of microplastic exposure, and chemical exposure in the case of superoxide dismutase and lipid peroxidation.